PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA YANG MENGAKIBATKAN LUKA BERAT (STUDI PUTUSAN NOMOR: 992 K/PID.SUS/2017) - Rahmatulloh, AA; Amsori, Amsori (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2022)
This study aims to determine the legal protection for victims of domestic violence and to find out the judge's legal considerations in making decisions on cases of criminal acts of domestic violence that resulted in serious injuries in case Number: 992 K/Pid.sus/2017. The type of research in this thesis is Juridical Normative Law Research. Normative Legal Research is a legal research method that principally conducts research on legal rules in legislation, jurisprudence and doctrine which is carried out qualitatively. From the research conducted, the authors get the following results: First, that legal protection for victims of criminal acts of domestic violence is an effort to recover victims of domestic violence, which is an integral part of the legal process. In this case, it is a shared responsibility between the government and service providers, including medical, psychological, legal and safe house services. Second, that based on the author's analysis, the consideration of the Supreme Court Judge in case Number: 992 K/Pid.Sus/2017 contradicts the authority of the judex juris because he did not receive a cassation request from the Public Prosecutor who clearly questioned the application of the law in judex facti. So, the author should state that the Supreme Court Judge's Decision Number: 992 K/Pid.Sus/2017 does not contain a sense of justice and does not contain the principle of law enforcement.